Inhibitory effects of 2-methacryloyloxyethyl phosphorylcholine polymer on the adherence of bacteria causing upper respiratory tract infection. Issue 1 (1st January 2020) - Iuchi, Hiroyuki; Ohori, Junichiro; Kyutoku, Takayuki; Ito, Kotoko; Kawabata, Masaki
ABSTRACT: Objective: We aimed to investigate the inhibitory effect of 2-methacryloyloxyethyl phosphorylcholine (MPC) polymer on the adherence of Streptococcus pneumoniae (Spn) and nontypeable Haemophilus influenzae (NTHi) in vitro and in vivo . Materials and Methods: Phosphorylcholine (PC) expression of 21 strains each of Spn and NTHi was evaluated using fluorescence-activated cell sorting; the adherence of bacteria to Detroit 562 cells and to the nasal mucosa of BALB/c mice was determined. MPC polymer-mediated inhibitory effects were compared with PC-keyhole limpet hemocyanin (PC-KLH)-mediated inhibitory effects. Results: In vitro experiments showed that pretreatment with MPC polymer markedly inhibited the adherence of Spn and NTHi in a concentration dose–dependent manner independently of PC expression. No correlation was observed between PC expression and MPC polymer-mediated inhibitory effects. Contrarily, there was a significant negative correlation between PC-KLH-mediated inhibitory effects and PC expression in Spn and NTHi. The same results were obtained via in vivo experiments. The MPC polymer did not affect the histology of the nasal mucosa. Conclusions: MPC polymer might be effective to reduce the occurrence of upper respiratory tract infection caused by Spn and NTHi and could be applied for the development of local treatments, such as topical gargles and nebulizer medications.